Reforming policy, changing practices? : special education in Finland after educational reforms - Pulkkinen, Jonna (2019)
The aim of the research was to examine the changes in special education practices following the funding reform in 2010 and the reform of the Basic Education Act in 2011. The research focused on studying if the practices in municipalities and schools have changed according to the aims of the reforms. In addition, the research examined variations in the practices and changes among municipalities and schools as well as the factors that explained the variations. The research was based on three kinds of data: a survey of principals (N = 335), interviews with high-ranking ofﬁcials in the municipal education administration (N = 7), and the official statistics for special education in municipalities (N = 301) compiled by Statistics Finland. Survey and interview data were collected in the autumn of 2012, whereas the official statistics covered the years between 2008 and 2014. Overall, the changes in special education practices seemed to align with the aims of the reforms. The results indicated that the reforms had altered the share of students receiving special education. Moreover, practices related to early support had changed, albeit not only in the positive sense. Negative changes were also discerned, such as the decrease in resources of part-time special education. The practices of special education and changes to them varied among municipalities and schools. In particular, small and large municipalities and schools differed in both special education practices and the implementation of the reforms. The results suggest that the reforms have altered the use of special education resources and that there is a need to re-allocate the resources of special education in municipalities. The results of this research support the idea that while implementing a reform, local authorities adapt the new practices to existing structures. Accordingly, the local context and existing structures of special education play a role in how practices have changed after the reform. Consequently, resources and variation in local context and structures have to take into account when planning reforms and their implementation.